Writing Faith on the Frontier: The Christian and Missionary Alliance and the Life Histories of Religious Conversion among Guangxi’s Multiethnic Communities - NI, Buxiao (Journal of Research for Christianity in China (JRCC), 2025)
This article adopts the methodology of life history to investigate the processes of religious conversion among multiethnic communities in Guangxi’s frontier regions during the late Qing and Republican periods. As a site of ethnic convergence, Guangxi was both politically marginal within the Chinese state and characterized by diverse religious and cultural interactions. Drawing on archival records of the Christian and Missionary Alliance (C&MA) and related sources, this study reconstructs the lived experiences of Zhuang, Yao, and Dong communities in their encounters with Christianity. The research demonstrates that conversion was not a unidirectional acceptance of religion, but rather a historical process shaped by the intersection of ethnic identity, local culture, and religious practice. The life history approach reveals the agency of individuals in conversion: on the one hand, religious transformation was closely tied to collective memory, vernacular language, and local social networks; on the other hand, the missionary strategies of the C&MA and the responses of local believers jointly fashioned the multiple configurations of a “faith frontier.” This study argues that micro-narratives of life history deepen our understanding of the localization of Christianity and the multiethnic religious experience in Guangxi, while also supplementing existing church historiography that has primarily relied on macro-level narratives.
Keywords: life history; frontier; Christian and Missionary Alliance; Christian faith; multiethnic communities